Enhancement of fuel cell based energy sustainability for cell on wheels mobile base stations used in disaster areas - Unal, Sencer; Dagteke, Suleyman Emre (Pergamon-Elsevier Science Ltd, 2024)
In disaster areas, Cells on Wheels (COW) mobile infrastructures are one of the most widely used solutions to restore communications lost due to power grid collapse or physical damage. The biggest problem with such systems is the low operating time and the inability to ensure energy continuity due to logistical problems. In this proposed study, the solution to the stated problem is focused on, and the use of hydrogen, which is the most important energy option of the future, is proposed as an innovative approach. The PV-hydrogen/fuel cell hybrid energy generation and storage system ensures the continuity of energy required for COW. In this study, the system is analyzed under realistic conditions using radiation and temperature data from different seasons in the disaster area. The energy needed in the proposed system is provided by PV and fuel cell with a control strategy. In addition, the electrolyser in the system contributes to the continuity of the energy by producing hydrogen with the excess energy provided by the PV. COW mobile infrastructures, which have a working time of 3 h under normal conditions, have been provided with energy continuity throughout the day thanks to the proposed system. As a result, this study has revealed that it is a solution to an important problem, especially in disaster areas where information flow is very critical.
Keywords: Mobile base station; Cells on wheels; Fuel cell; Disaster areas; Sustainable energy